Kinetic Modelling of Betalain Stability and Color Changes in Yogurt During Storage - Onur Guneser (Polish Journal of Food and Nutrition Sciences)
Assessment of the storage stability of betalains added to food during processing is crucial to estimate the shelf-life of colored food products and the potency of natural food colorants. The stability of beetroot betalains in yogurt during storage was evaluated in this study. Kinetic experiments were conducted at storage temperatures of 4°C, 10°C, and 20°C. The relationships were also determined between the betalain degradation and lightness ( L* ), redness ( a* ), and yellowness ( b* ). First-order kinetics was observed in the betalain degradation, and the changes in color parameters of the yogurt samples fitted zero-order kinetics. The activation energy required for the degradation of betalains and changes in L*, a* , and b * was found as 104.9, 67.6, 76.5, and 86.1 kJ/mol, respectively. The half-life period of the degradation of red beet betalains was found as 51.43, 30.91, and 4.54 days at 4°C, 10°C, and 20°C, respectively. Multiple linear regression models were also established for betalain content and color parameters. There was a decrease in betalain content and a* color value in the yogurt colored with a beetroot extract during storage. A significant positive correlation was found between pH, a* value, and betalain content in yogurt, while a significant negative correlation was found between betalain content and L* and b* values. Further studies need to be carried out to reveal the relationship between color parameters and natural pigments in food systems.